Uncovering novel susceptibility targets to enhance the efficacy of third-generation cephalosporins against ESBL-producing uropathogenic Escherichia coli. (19th February 2020) - Phan, Minh-Duy; Bottomley, Amy L; Peters, Kate M; Harry, Elizabeth J; Schembri, Mark A
Abstract: Background: Uropathogenic Escherichia coli (UPEC) are a major cause of urinary tract infection (UTI), one of the most common infectious diseases in humans. UPEC are increasingly associated with resistance to multiple antibiotics. This includes resistance to third-generation cephalosporins, a common class of antibiotics frequently used to treat UTI. Methods: We employed a high-throughput genome-wide screen using saturated transposon mutagenesis and transposon directed insertion-site sequencing (TraDIS) together with phenotypic resistance assessment to identify key genes required for survival of the MDR UPEC ST131 strain EC958 in the presence of the third-generation cephalosporin cefotaxime. Results: We showed that bla CMY-23 is the major ESBL gene in EC958 responsible for mediating resistance to cefotaxime. Our screen also revealed that mutation of genes involved in cell division and the twin-arginine translocation pathway sensitized EC958 to cefotaxime. The role of these cell-division and protein-secretion genes in cefotaxime resistance was confirmed through the construction of mutants and phenotypic testing. Mutation of these genes also sensitized EC958 to other cephalosporins. Conclusions: This work provides an exemplar for the application of TraDIS to define molecular mechanisms of resistance to antibiotics. The identification of mutants that sensitize UPEC to cefotaxime, despite the presence of a cephalosporinase, provides a framework for the development of new approaches to treat infections caused by MDR pathogens.